Financial efficiency of microfinance institutions in the event of pre and post financial crisis - Bakri, Mohammed Hariri; Zainal, Nurazilah; Mohd Sanusi, Zuraidah; Abdul Razak, Norshuhaida; Roslan, Sarah; Harjito, Dwipraptono Agus (SRAC - Romanian Society for Quality, 2022)
The 2008 financial crisis hits economic growth particularly in banking sector. The impacts also not spared to Microfinance Institutions' (MFIs) since MFIs nowadays become integral part in financial system. This paper aims to evaluate financial efficiency of the MFIs in the period of pre and post-financial crisis in first objective. Next, to examine impact of firm characteristics and economic determinants on financial efficiency within the similar period. Total of 166 MFIs from ASEAN 4 countries were selected which include Vietnam, Cambodia, Indonesia, and the Philippines between pre-crisis years, 2000-2007 and post-crisis years, 2010-2017. Using Data Envelopment Analysis, first stage analysis estimates level of financial efficiency of MFIs. In second stage, application of Multivariate Panel Regression Analysis evaluates the effects of firm characteristics and economic determinants on financial efficiency level of the MFIs. Result on first stage revealed the post-crisis efficiency score higher than the pre-crisis efficiency score and this implies financial crisis does not financially affected the MFIs hence appear to be sustainable in the long-run. The findings in the next stage reveal firm characteristics and economic determinants mostly found insignificant for post crisis period while significant in the pre-crisis. The insignificant outcomes prove the crisis has resulted some variables being unable to explain variation in financial efficiency of the MFIs. Generally, the microfinance industry will be benefited from this study as an input for any concurrent crisis in the future. This is vital since the MFIs is the only financial institutions that provide financial access to the poor.